The Meaning of Life in Cottingham Viewpoint - Amirabbas Aizamani; Maryam Daryaniasl (Comparative Theology, 2010)
Questioning the ‘ Meaning of Life ’ is one of the most important issues that has been asked during the history. But how to question and answer to it is more curiously concerned in the modern time. In answering to the question ‘ what is the meaning of life? ’ there have been proposed various ideas. In this article‚ we explain the John Cottingham ’s idea on this issue.